2021
DOI: 10.1021/acsphotonics.1c01128
|View full text |Cite
|
Sign up to set email alerts
|

Reconfigurable Low-Emissivity Optical Coating Using Ultrathin Phase Change Materials

Abstract: A method for controlling the optical properties of a solid-state film over a broad wavelength range is highly desirable and could have significant commercial impact. One such application is smart glazing technology where near-infrared solar radiation is harvested in the winter and reflected it in the summeran impossibility for materials with fixed thermal and optical properties. Here, we experimentally demonstrate the first spectrally tunable, low-emissivity coating using a chalcogenidebased phase-change mate… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
21
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
8
1

Relationship

1
8

Authors

Journals

citations
Cited by 24 publications
(21 citation statements)
references
References 54 publications
0
21
0
Order By: Relevance
“…Single-doped heaters can therefore be used for waveguides, but also for larger PICs components such as MMIs and even to fit large metasurfaces. Other alternatives for transparent microheaters, already demonstrated to switch PCMs, might be considered to avoid doping losses overall and extend the transparency window to shorter wavelengths, such as graphene, [38,40] fluorine-doped tin oxide, [41] and indium-tin-oxide; [39,42] however, their full integration and reversible cyclability on integrated waveguides is yet to be demonstrated. We draw a direct comparison between our PCM approach and other phase-shifting approaches in Table 1 considering 10-90% rise time, the total change in the effective index, ∆n eff , the total length and voltage to achieve a π phase shift, L π and V π , and the insertion loss (IL).…”
Section: Discussionmentioning
confidence: 99%
“…Single-doped heaters can therefore be used for waveguides, but also for larger PICs components such as MMIs and even to fit large metasurfaces. Other alternatives for transparent microheaters, already demonstrated to switch PCMs, might be considered to avoid doping losses overall and extend the transparency window to shorter wavelengths, such as graphene, [38,40] fluorine-doped tin oxide, [41] and indium-tin-oxide; [39,42] however, their full integration and reversible cyclability on integrated waveguides is yet to be demonstrated. We draw a direct comparison between our PCM approach and other phase-shifting approaches in Table 1 considering 10-90% rise time, the total change in the effective index, ∆n eff , the total length and voltage to achieve a π phase shift, L π and V π , and the insertion loss (IL).…”
Section: Discussionmentioning
confidence: 99%
“…In particular, electro-thermal methods that enable scalable onchip integration have been explored in several recent studies. [39][40][41][42][43][44] The heater materials used include metals, [45] transparent conducting oxides (TCOs), [46][47][48][49] and doped silicon. While metals are useful for free-space reflective devices, they introduce significant optical losses in transmissive or waveguide components.…”
Section: Introductionmentioning
confidence: 99%
“…There are predominantly two types of electrical heaters: (1) doped intrinsic semiconductor, such as silicon, on which the PICs are fabricated; ,, and (2) extrinsic heaters, such as metal, graphene, , indium-doped tin oxide (ITO), , or fluorine-doped tin oxide (FTO) . A detailed simulation study of different heaters revealed that graphene heaters are much more electrical energy-efficient than doped semiconductors (such as PIN diode-based silicon heaters) or ITO heaters, primarily because of graphene’s much smaller active volume.…”
Section: Review Of Phase-change Materials Photonicsmentioning
confidence: 99%
“…There are predominantly two types of electrical heaters: (1) doped intrinsic semiconductor, such as silicon, on which the PICs are fabricated; 45,83,87 and (2) extrinsic heaters, such as metal, 85 graphene, 88,89 indium-doped tin oxide (ITO), 84,86 or fluorine-doped tin oxide (FTO). 90 A detailed simulation study of different heaters revealed that graphene heaters are much more electrical energy-efficient than doped semiconductors (such as PIN diode-based silicon heaters) or ITO heaters, 91 primarily because of graphene's much smaller active volume. On the other hand, PIN silicon heaters have a better heating efficiency than metal heaters 92 because the latter must be placed far from optical modes to avoid high absorption loss, reducing the thermal efficiency and optical contrast.…”
Section: Photonicsmentioning
confidence: 99%